Evaluation of the optimum number, capacity, and location of tie-lines for the interconnection of Visayas and Mindanao - Mendoza, Jeramy Castro (2011)
The Philippine electric power system is composed of the already interconnected Luzon and Visayas Grids, and the isolated Mindanao Grid. Plans for interconnection between the Visayas and Mindanao Grids are part of the Indicative Plans in the Transmission Development Plan 2010 of the National Grid Corporation of the Philippines (NGCP) for 2015 and beyond. Interconnection will improve power system reliability and may lower total reserve capacity requirements. The objective of this project was to determine the optimal capacity, number, and location of tie-lines for the interconnection of the Visayas and Mindanao Grids that provides acceptable loss-of-load expectation (LOLE) over the planning horizon at minimum life cycle cost. Visayas and Mindanao Grid data were gathered from the NGCP. To determine optimal interconnection, Genetic Algorithm (GA) with LOLE constraints was used. Power flow analysis was used to determine the total electrical losses in both systems. Based on compatibility of voltage levels and locations of transmission substations, we identified four possible interconnection options: (1) Ormoc-Tagoloan, (2) Ubay-Tagoloan, (3) Ormoc-Placer, and (4) Ormoc-Ubay-Tagoloan. These locations, as well as their combinations, were analyzed. The optimal Visayas-Mindanao interconnection project determined a 330-MW 250-kV HVDC link between Ormoc and Placer Substations.
Undergraduate student project (B.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Interconnected electric utility systems; Electric power-plants -- Philippines; Electric power systems